Ancestry Single Nucleotide Polymorphisms in Malayo-Polynesian Sub-Groups in the Malay Population: A Preliminary Study - Norazzman, Nur Iffah; Assyuhada, Mat Ghani Siti; Daud, Nuur; Mazuki, Noorzalifah; Musa, Nurul; Hassan, Sharifah; Bahri, Ayunni; Adeeb, Naam; Hassan, Nik; Yunus, Nazihah; Sidek, Mohamad; Musa, Mohamad; et al. (Jordan Medical Journal, 2023)
Malay populations are sub-groups of the Malayo-Polynesian, with various sub-ethnic groups believed to have different ancestral origins based on their migration centuries ago. The variability in the genetic pattern within the Malay population might impose different risk and disease probabilities or certain phenotypes. This study aimed to analyze single nucleotide polymorphisms (SNPs) in Malayo-Polynesian sub-groups of the Malay population in Southeast Asia. SNPs were genotyped through T-ARMS PCR in 52 unrelated individuals from three Malay sub-groups: Champa (n=16), Kelantan (n=25) and Bugis (n=11). Most (60%) of the SNP genotypes showed a similarity with all Malay sub-ethnic groups. The PCA plot showed that all Malay sub-ethnic groups were slightly separated but clustered together with Asian populations compared with population groups from other geographical regions. Overall, the SNP genotyping generated from this study provides essential knowledge of the genetic relationships within Malay sub-ethnic groups in Southeast Asia and other global populations. Additionally, these findings may be used for future illness research, drug response estimation, and the development of preventive and therapeutic management strategies toward more personalized or precision medicine. Malay populations are sub-groups of the Malayo-Polynesian, with various sub-ethnic groups believed to have different ancestral origins based on their migration centuries ago. The variability in the genetic pattern within the Malay population might impose different risk and disease probabilities or certain phenotypes. This study aimed to analyze single nucleotide polymorphisms (SNPs) in Malayo-Polynesian sub-groups of the Malay population in Southeast Asia. SNPs were genotyped through T-ARMS PCR in 52 unrelated individuals from three Malay sub-groups: Champa (n=16), Kelantan (n=25) and Bugis (n=11). Most (60%) of the SNP genotypes showed a similarity with all Malay sub-ethnic groups. The PCA plot showed that all Malay sub-ethnic groups were slightly separated but clustered together with Asian populations compared with population groups from other geographical regions. Overall, the SNP genotyping generated from this study provides essential knowledge of the genetic relationships within Malay sub-ethnic groups in Southeast Asia and other global populations. Additionally, these findings may be used for future illness research, drug response estimation, and the development of preventive and therapeutic management strategies toward more personalized or precision medicine.